Lanthanum-strontium-cobalt-iron perovskite catalyst and preparation method and low-temperature denitration method thereof

By developing the lanthanum strontium cobalt iron perovskite catalyst, using its perovskite structure and oxidation properties of doped elements, the problem of insufficient denitrification activity at low temperatures is solved, and the effect of efficient denitrification at low temperatures is achieved, saving energy and reducing CO2 emissions is achieved.

CN119793476APending Publication Date: 2025-04-11MCC CAPITAL ENGINEERING & RESEARCH INC LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901569.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing NH3-SCR catalysts are insufficient in denitrification under low temperature conditions and require medium and high temperature heating to activate the catalyst, resulting in an increase in energy consumption and CO2 emissions.

Method used

A lanthanum strontium cobalt iron perovskite catalyst was developed, which has ABO3 perovskite structure and doping elements, and is prepared by sol-gel method to improve the oxygen vacancies and oxidation properties of the catalyst, thereby assisting the NH3-SCR reaction under low temperature conditions.

Benefits of technology

The catalyst exhibits good NO oxidation performance in the low temperature range of 150-450°C, and can assist the NH3-SCR reaction at lower temperatures, reduce the reaction temperature of the catalyst, save energy consumption and reduce CO2 emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793476A_ABST
    Figure CN119793476A_ABST
Patent Text Reader

Abstract

The invention provides a lanthanum-strontium-cobalt-iron perovskite catalyst and a preparation method and a low-temperature denitration method thereof. The molecular formula of the perovskite catalyst is LaxSr (1-x) CoyFe (1-y) O3, x ranges from 0.7 to 1, and y ranges from 0.6 to 1. The preparation method of the catalyst adopts a sol-gel method. The invention also provides an application of the perovskite catalyst as an NO oxidation catalyst, and a composite catalytic system formed by the perovskite catalyst and an NH3-SCR catalyst. The invention also provides a low-temperature denitration method using the composite catalytic system. The perovskite catalyst has good NO oxidation catalytic performance at low temperature, and can assist the NH3-SCR catalyst to generate rapid NH3-SCR catalytic reaction after being compounded with the NH3-SCR catalyst, so that the reaction temperature of the catalyst is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of SCR denitration, and in particular to a lanthanum strontium cobalt iron perovskite catalyst and a preparation method thereof and a low-temperature denitration method. Background Art

[0002] Nitrogen oxides (NO x ) is one of the main pollutants in the atmosphere, which not only causes acid rain, photochemical smog and ozone layer depletion, but also seriously endangers life and health on Earth. Steel sintering flue gas is a major source of NOx emissions. Selective catalytic reduction (SCR) refers to the process of adding an additional reducing agent to the reaction system to selectively reduce NO in the atmosphere under the condition of excess O2. x Reduced to non-toxic and harmless N2. Selective catalytic reduction is currently the most effective and widely used NO reduction method under oxygen-rich conditions. x Removal technology. Depending on the added reducing agent, SCR technology mainly includes hydrocarbon selective catalytic reduction (HC-SCR) and ammonia selective catalytic reduction (NH3-SCR).

[0003] Ammonia selective catalytic reduction (NH3-SCR) is currently the most effective method for removing nitrogen oxides. The NH3-SCR reaction is divided into standard NH3-SCR and fast NH3-SCR, and their reaction equations are as follows:

[0004] 4NO+4NH3+O2→4N2+6H2O (standard NH3-SCR)

[0005] NO+NO2+2NH3→N2+3H2O (fast NH3-SCR)

[0006] NH3-SCR reaction can effectively remove NOx. Since the 1970s, NH3-SCR technology has been industrially applied to stationary sources of NO such as coal-fired power plant exhaust. x Under humid, oxygen-rich, and sulfur-containing conditions, the catalyst using this technology still has high activity and long service life. When this technology is used to remove NOx from diesel vehicle exhaust under oxygen-rich conditions, there will be problems such as ammonia leakage and difficulty in storage and transportation. Therefore, urea hydrolysis is often used to produce ammonia. Generally speaking, the following reactions occur on the catalyst surface.

[0007] 4NO+4NH3+O2→4N2+6H2O(1.1)

[0008] 2NO2+4NH3+O2→3N2+6H2O(1.2)

[0009] 2NO+2NO2+4NH3→4N2+6H2O(1.3)

[0010] Formula (1.1) is the equation for the "standard SCR" reaction, in which the stoichiometric ratios of NH3 and NO are the same. Formula (1.3) is the reaction process of "fast SCR", and its reaction rate above 200°C is more than 10 times that of "standard SCR".

[0011] The most widely used vanadium-based standard NH3-SCR denitrification technology has an optimal reaction window temperature between 250 and 450°C, while the sintering flue gas temperature is relatively low (110-200°C). In response to this problem, steel companies currently widely use medium and high temperature SCR denitrification technology, which heats the flue gas to the medium and high temperature catalyst reaction temperature through a flue gas heat exchanger or combustion heating for denitrification reaction. The sintering flue gas needs to be heated to above 260°C, which will cause energy consumption and produce a large amount of CO2, and a low-temperature catalyst needs to be developed.

[0012] The core of NH3-SCR technology is the catalyst. The current NH3-SCR catalysts can be divided into three categories: vanadium-based oxide catalysts, non-vanadium-based metal oxide catalysts, and transition metal-loaded molecular sieve catalysts.

[0013] Nitrogen oxides in fixed sources mainly come from the tail gas of coal-fired power plants and the sintering flue gas of steel plants. In the 1970s, people developed V2O5-WO3(MoO3) / TiO2 catalyst and successfully applied it to the removal of NOx from fixed sources. At present, it has become the most widely used NH3-SCR catalyst in industry. The main active center of V2O5-WO3(MoO3) / TiO2 is V2O5, the carrier is TiO2, and the additive is WO3 or MoO3, which is used to improve the surface acidity, catalytic activity and stability of the catalyst. The catalyst shows good NOx removal effect in the medium temperature section (250-400℃) and has good sulfur resistance. However, in practical applications, taking the steel industry as an example, the sintering flue gas temperature is low (120-180℃), and the denitrification activity of V2O5-WO3(MoO3) / TiO2 catalyst in this temperature range is difficult to meet the requirements, and additional heating devices are usually required. This will increase costs and cause waste of resources and energy. In addition, vanadium is biologically toxic and volatilizes at high temperatures, which is not conducive to the removal of nitrogen oxides and will further damage the ecological environment. Therefore, it is necessary to develop other types of catalysts.

[0014] In recent years, a variety of transition metal oxides (MnOx, FeOx, CeOx, etc.) have attracted the attention of researchers due to their good low-temperature NH3-SCR catalytic performance. Some Ce-based catalysts have been industrialized, but their preparation costs are high. It is worth noting that fixed source flue gas contains a lot of dust, water and SO2. Therefore, flue gas usually undergoes dust removal and desulfurization processes before NH3-SCR denitrification. A variety of transition metal oxides (MnOx, FeOx, CeOx, etc.) have attracted attention due to their good low-temperature NH3-SCR catalytic performance. Some Ce-based catalysts have been industrialized, but their preparation costs are high. Therefore, it is necessary to develop simpler and cheaper catalyst preparation and modification methods in the future to reduce the cost of catalysts. Summary of the invention

[0015] In order to solve the above problems, the purpose of the present invention is to provide a lanthanum strontium cobalt iron perovskite catalyst and its preparation method and low-temperature denitration method. The perovskite catalyst has good NO oxidation catalytic performance at low temperature, and after being combined with the NH3-SCR catalyst, it can assist the NH3-SCR catalyst to produce a rapid NH3-SCR catalytic reaction, thereby reducing the reaction temperature of the catalyst.

[0016] In order to achieve the above object, the present invention provides a lanthanum strontium cobalt iron perovskite catalyst, the molecular formula of the catalyst is La x Sr 1-x Co y Fe 1-y O3, wherein x is 0.7-1 and y is 0.6-1.

[0017] The lanthanum strontium cobalt iron perovskite catalyst provided by the present invention has an ABO3 type perovskite structure. The catalyst can be regarded as being formed by doping Sr and Fe on the basis of LaCoO3. Sr can partially replace La, and Fe can partially replace Co. The perovskite catalyst has a perovskite structure and contains doping elements, which can produce more oxygen vacancies and better oxidizability, thereby improving the catalytic performance of the catalyst.

[0018] In the above lanthanum strontium cobalt iron perovskite catalyst, x may indicate the degree of replacement of La by Sr. x is generally 0.7-1, for example, specific values ​​such as 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, and ranges with any two of the above specific values ​​as endpoints.

[0019] In the above lanthanum strontium cobalt iron perovskite catalyst, y can indicate the degree of replacement of Co by Fe. y is generally 0.6-1, for example, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 and other specific values, and ranges with any two of the above specific values ​​as endpoints.

[0020] In the above lanthanum strontium cobalt iron perovskite catalyst, the valence states of La, Co, and Fe are all +3, and Sr is +2. It is understandable that the above lanthanum strontium cobalt iron perovskite catalyst has oxygen vacancy defects, so the total valence of the molecular formula is not 0.

[0021] According to a specific embodiment of the present invention, the particle size of the lanthanum strontium cobalt iron perovskite catalyst may be 0.25 μm-1 μm, specifically 0.25 μm, 0.50 μm, 0.75 μm, 1.0 μm and other specific values, as well as a range with any two of the above specific values ​​as endpoints.

[0022] According to a specific embodiment of the present invention, the crystallinity of the lanthanum strontium cobalt iron perovskite catalyst may be greater than or equal to 70%.

[0023] The present invention also provides a preparation method of the above-mentioned lanthanum strontium cobalt iron perovskite catalyst, which comprises: mixing a metal salt precursor with a chelating agent to obtain a raw material solution; removing the solvent from the raw material solution to form a gel, drying the gel to form a dry gel, and calcining the dry gel to obtain the lanthanum strontium cobalt iron perovskite catalyst; wherein the metal salt precursor comprises a lanthanum salt, a strontium salt, a cobalt salt and an iron salt; and the molar ratio of the chelating agent to all metal ions in the metal salt precursor is 1-3:1.

[0024] The above preparation method prepares the perovskite catalyst by the sol-gel method. Compared with other preparation methods such as precipitation method, the sol-gel method can make the distribution of active components in the catalyst uniform, which helps to improve the catalytic performance and stability of the catalyst. The metal salt precursor used is generally a metal soluble salt, such as metal nitrate, soluble metal chloride, soluble metal sulfate, etc. When using a metal precursor to prepare a metal oxide, a chelating agent is generally added, and the chelating agent can act as a template in the process of synthesizing a perovskite structure catalyst.

[0025] In the preparation method of the lanthanum strontium cobalt iron perovskite catalyst, the lanthanum salt may be a soluble salt of lanthanum, such as lanthanum nitrate and / or lanthanum chloride, and specifically may be lanthanum nitrate hexahydrate. The lanthanum in the lanthanum salt has a valence of +3.

[0026] In the preparation method of the lanthanum strontium cobalt iron perovskite catalyst, the strontium salt can be a soluble salt of strontium, for example, strontium nitrate and / or strontium chloride. The strontium in the strontium salt has a valence of +3.

[0027] In the preparation method of the lanthanum strontium cobalt iron perovskite catalyst, the cobalt salt can be a soluble salt of cobalt, for example, one or a combination of two or more of cobalt nitrate, cobalt chloride, and cobalt sulfate, specifically cobalt nitrate hexahydrate. The cobalt in the cobalt salt is +2 valence.

[0028] In the preparation method of the lanthanum strontium cobalt iron perovskite catalyst, the iron salt can be a soluble salt of iron, for example, one or a combination of two or more of iron nitrate, iron chloride, and iron sulfate, specifically iron nitrate nonahydrate. The iron in the iron salt is +3 valence.

[0029] In the preparation method of the lanthanum strontium cobalt iron perovskite catalyst, the amount of the lanthanum salt, strontium salt, cobalt salt and iron salt can be determined according to the content of each metal element in the lanthanum strontium cobalt iron perovskite catalyst.

[0030] In the preparation method of the above lanthanum strontium cobalt iron perovskite catalyst, the chelating agent includes citric acid (CA) and / or ethylenediaminetetraacetic acid (EDTA).

[0031] In some specific embodiments, the EDTA can be added in the form of a solution, and the pH value of the EDTA solution is 3-6, and this pH value range allows EDTA to be fully dissolved. More specifically, the pH value of the EDTA solution can be adjusted by a pH adjuster, and the pH adjuster includes ammonia water.

[0032] In the preparation method of the above-mentioned lanthanum strontium cobalt iron perovskite catalyst, the molar ratio of the chelating agent to all metal ions in the metal salt precursor is generally controlled to be 1-3:1, for example, it can be specific values ​​such as 1:1, 1.5:1, 2:1, 2.5:1, 3:1, and a range with any two of the above-mentioned specific values ​​as endpoints.

[0033] In the above method for preparing the lanthanum strontium cobalt iron perovskite catalyst, the temperature for mixing the metal salt precursor and the chelating agent may be 50°C-90°C.

[0034] In the above-mentioned method for preparing the lanthanum strontium cobalt iron perovskite catalyst, the pH value of the raw material solution is 3-6. This pH value can ensure that the chelating agent is fully dissolved in the raw material solution and can avoid the pre-hydrolysis of the metal salt precursor. In some specific embodiments, the pH value of the raw material solution can be adjusted by a pH adjuster, and the pH adjuster can include ammonia water.

[0035] In some specific embodiments, the raw material solution may be a purple-red clear solution and / or sol.

[0036] In the above-mentioned method for preparing the lanthanum strontium cobalt iron perovskite catalyst, the method for removing the solvent includes but is not limited to rotary evaporation, ordinary evaporation and other methods that can form a gel.

[0037] In the preparation method of the above-mentioned lanthanum strontium cobalt iron perovskite catalyst, when the solvent is removed by rotary evaporation to form a gel, the rotation speed of the rotary evaporation is 10rpm / min-60rpm / min, the temperature of the rotary evaporation is 50℃-90℃, and the time of the rotary evaporation is 8h-24h.

[0038] In some specific embodiments, the gel obtained by rotary evaporation can be a viscous purple-red gel.

[0039] In the above-mentioned method for preparing the lanthanum strontium cobalt iron perovskite catalyst, the drying gas pressure is 2000Pa-10000Pa, and the drying temperature is 120°C-170°C.

[0040] In the above-mentioned method for preparing the lanthanum strontium cobalt iron perovskite catalyst, the calcination may be a step-by-step calcination, and specifically may include a first calcination and a second calcination performed sequentially.

[0041] In the preparation method of the above-mentioned lanthanum strontium cobalt iron perovskite catalyst, the first calcination can be used to remove organic matter (such as EDTA, CA, etc.). The temperature of the first calcination can be 300°C-400°C, and can be specifically 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, and other specific values, as well as a range with any two of the above specific values ​​as endpoints; the time of the first calcination is 3h-7h.

[0042] In the preparation method of the above-mentioned lanthanum strontium cobalt iron perovskite catalyst, the temperature of the second calcination is 750°C-850°C, and specifically can be 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C and other specific values, as well as a range with any two of the above specific values ​​as endpoints; the time of the second calcination is 5h-8h.

[0043] In some specific embodiments, the calcining can be performed in a muffle furnace.

[0044] According to a specific embodiment of the present invention, the preparation method of the lanthanum strontium cobalt iron perovskite catalyst may specifically include:

[0045] Mixing a metal salt precursor (lanthanum salt, cobalt salt, strontium salt and iron salt) and a chelating agent (at least one of EDTA and CA), adjusting the pH to 3-6, and obtaining a raw material solution; wherein the molar ratio of the chelating agent to the metal ion of the metal salt precursor is 1-3:1;

[0046] The raw material solution was rotary evaporated at 10-60 rpm / min and 50-90° C. for 8-24 h to obtain a gel;

[0047] The gel is vacuum dried at an air pressure of 2000-10000 Pa and a temperature of 120-170° C. to obtain a dry gel;

[0048] The dry gel is first calcined at 300-400°C for 3-7h to remove organic matter; and then secondly calcined at 750-850°C for 5-8h to obtain a lanthanum strontium cobalt iron perovskite catalyst.

[0049] The present invention also provides a NO oxidation catalyst, which comprises the above-mentioned lanthanum strontium cobalt iron perovskite catalyst or is made of the above-mentioned lanthanum strontium cobalt iron perovskite catalyst. The above-mentioned lanthanum strontium cobalt iron perovskite catalyst provided by the present invention has good NO oxidation performance in the low temperature range (150-450°C) and can be used as a NO oxidation catalyst.

[0050] The present invention also provides a composite catalytic system, which comprises the above-mentioned NO oxidation catalyst and NH3-SCR catalyst provided by the present invention.

[0051] In the above-mentioned composite catalytic system, the mass ratio of the NO oxidation catalyst to the NH3-SCR catalyst is generally 1:1-2, for example, specific values ​​such as 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, and a range with any two of the above-mentioned specific values ​​as endpoints.

[0052] In the above composite catalytic system, the NH3-SCR catalyst includes a V2O5-WO3 / TiO2 catalyst.

[0053] According to a specific embodiment of the present invention, based on the total mass of the V2O5-WO3 / TiO2 catalyst being 100%, the mass fractions of the components in the V2O5-WO3 / TiO2 catalyst are as follows: the mass fraction of V2O5 is 0.1-1wt.%, the mass fraction of WO3 is 1-10wt.%, and the remainder is TiO2. Among them, V2O5 is the active center, WO3 is the auxiliary agent, and TiO2 is the carrier.

[0054] According to a specific embodiment of the present invention, the preparation method of the above-mentioned V2O5-WO3 / TiO2 catalyst may include: mixing a titanium source, a vanadium source and a tungsten source, performing a hydrothermal reaction, filtering, drying and calcining to obtain the V2O5-WO3 / TiO2 catalyst.

[0055] In the preparation method of the above V2O5-WO3 / TiO2 catalyst, the titanium source is used as a precursor of titanium dioxide, and the titanium source may include metatitanic acid.

[0056] In the preparation method of the above V2O5-WO3 / TiO2 catalyst, the vanadium source may include ammonium metavanadate.

[0057] In the above-mentioned method for preparing the V2O5-WO3 / TiO2 catalyst, the tungsten source may include ammonium metatungstate.

[0058] In the preparation method of the above-mentioned V2O5-WO3 / TiO2 catalyst, the temperature of the hydrothermal reaction is 150°C-250°C, and the time of the hydrothermal reaction is 8h-24h.

[0059] In the preparation method of the above V2O5-WO3 / TiO2 catalyst, the drying temperature is 100°C-160°C, and the drying time is 8h-24h.

[0060] In the preparation method of the V2O5-WO3 / TiO2 catalyst, the calcination temperature is 400°C-650°C, the calcination time is 4h-12h, and the calcination can be carried out in an air atmosphere.

[0061] The composite catalytic system provided by the present invention can be used as a fast NH3-SCR-assisted denitration composite catalyst. The composite catalytic system is applied to the selective catalytic reduction reaction of ammonia, which can reduce the temperature required for the reduction reaction and improve the reaction efficiency.

[0062] The present invention also provides a low-temperature denitration method, which comprises: using the above-mentioned composite catalytic system provided by the present invention as a catalyst, introducing raw flue gas containing NO and NH3 for denitration; wherein the NO oxidation catalyst and the NH3-SCR catalyst of the composite catalytic system are placed separately so that the raw flue gas first contacts the NO oxidation catalyst and then contacts the NH3-SCR catalyst.

[0063] According to a specific embodiment of the present invention, the above-mentioned low-temperature denitrification method may specifically include: introducing raw flue gas, allowing the raw flue gas to contact with a NO oxidation catalyst to perform a NO oxidation reaction; mixing the flue gas after the NO oxidation reaction with NH3 to form a mixed flue gas, and contacting the mixed flue gas with an NH3-SCR catalyst to perform an SCR reaction to complete denitrification.

[0064] The denitration process of the above-mentioned low-temperature denitration method provided by the present invention is mainly divided into two stages: in the first stage, the NO oxidation catalyst catalyzes the oxidation reaction of the raw flue gas containing NO to oxidize at least part of the NO into NO2; in the second stage, NH3 is introduced, and NH3 is mixed with the raw flue gas (containing NO2) that has undergone the NO oxidation reaction to form a mixed flue gas, and the mixed flue gas is contacted with the NH3-SCR catalyst for SCR reaction. Since the mixed flue gas contains NO2, the SCR reaction in the second stage is a fast SCR reaction, and the reaction equation is: NO+NO2+2NH3→N2+3H2O. Compared with the standard SCR reaction (the equation is 4NO+4NH3+O2→4N2+6H2O), the fast SCR reaction has a low activation energy and a high reaction rate, and can react quickly without a catalyst. The present invention introduces a NO oxidation catalyst into the catalyst system of the SCR reaction, oxidizes NO into NO2 through an oxidation reaction, and provides a prerequisite for a fast SCR reaction, thereby coupling a fast NH3-SCR reaction on the basis of a standard NH3-SCR reaction, thereby improving the low-temperature reaction performance of the catalyst. In addition, after the NO oxidation reaction, the flue gas temperature will not increase significantly, the overall temperature of the denitration process is not high, and the temperature resistance requirements for the reaction device to achieve the denitration process are not high.

[0065] The above-mentioned low-temperature denitrification method is a fast NH3-SCR-assisted ammonia selective catalytic reduction reaction. By adding a NO oxidation catalyst before the NH3-SCR catalyst, NO is pre-oxidized to produce NO2, which assists the NH3-SCR catalyst to produce a fast NH3-SCR catalytic reaction, thereby reducing the reaction temperature of the catalyst, saving the energy consumption required for heating and the large amount of CO2 generated thereby.

[0066] In the above-mentioned low-temperature denitrification method, the raw flue gas contains NO, O2, H2O, SO2 and N2; specifically, the composition of the raw flue gas can be: NO with a concentration of 100ppm-1000ppm, O2 with a volume fraction of 5%-10%, H2O with a volume fraction of 2%-5%, SO2 with a concentration of 0-200ppm, and the remainder is N2 (that is, nitrogen is the balance gas).

[0067] In the above-mentioned low-temperature denitration method, the raw flue gas is generally introduced first for NO oxidation reaction, and then NH3 is introduced for SCR reaction after NO2 is generated. The molar ratio of NO to NH3 in the raw flue gas can be 1:1-1.2, and can be specifically 1:1, 1:1.0.5, 1:1.1, 1:1.5, 1:2, and the like, and a range with any two of the above-mentioned specific values ​​as endpoints, for example, 1:1.

[0068] In the above-mentioned low-temperature denitrification method, the ratio of the molar amount of NO in the raw flue gas to the mass of the composite catalytic system can be controlled to be 1 mol: 0.5-2 g, for example, specific values ​​such as 1 mol: 0.5 g, 1 mol: 1 g, 1 mol: 1.5 g, 1 mol: 2 g, and a range with any two of the above-mentioned specific values ​​as endpoints.

[0069] In some specific embodiments, the mass ratio of NO in the raw flue gas, NH3 (as raw material), and the composite catalytic system can be controlled to be 1 mol: 1 mol: 0.5-2 g.

[0070] In the above low-temperature denitration method, the reaction temperature of the denitration is 150°C-450°C, and can be specifically 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, and other specific values, as well as a range with any two of the above specific values ​​as endpoints. Further, the reaction temperature of the denitration can be 150-300°C.

[0071] In the above low-temperature denitration method, the reaction pressure of the denitration is 0.1MPa-0.6MPa, and specifically can be 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa and other specific values, and a range with any two of the above specific values ​​as endpoints. Further, the reaction pressure of the denitration can be 0.1-0.5MPa, and further can be 0.1-0.3MPa.

[0072] In the above low-temperature denitration method, the reaction space velocity of the denitration is 5000-160000h -1 , specifically 5000h -1 、10000h -1 、20000h -1 、30000h -1 、40000h -1 、50000h -1 、60000h -1 、80000h -1 、100000h - 1 、120000h -1 、140000h -1 、160000h -1 The above specific values ​​and ranges with any two of the above specific values ​​as endpoints. Further, the reaction space velocity of the denitrification can be 5000-120000h -1 , further can be 10000-50000h -1 .

[0073] The NO oxidation reaction and SCR reaction in the denitration method of the present invention can be carried out under the above conditions (150°C-450°C, 0.1MPa-0.6MPa, 5000-160000h -1 )conduct.

[0074] According to a specific embodiment of the present invention, the specific process of the above-mentioned low-temperature denitration method can be: in a reaction device, a NO oxidation catalyst is placed on the uppermost layer, an ammonia injection device (for providing ammonia) is set below the NO oxidation catalyst, and an NH3-SCR catalyst is placed below the ammonia injection device; the temperature, air velocity, pressure and other denitration reaction conditions of the reaction device are set to perform denitration. When performing denitration, the raw flue gas containing NO is first introduced into the reaction device, and the raw flue gas first contacts with the NO oxidation catalyst on the upper layer, and a NO oxidation reaction occurs to generate NO2; then the flue gas containing NO2 passes through the ammonia injection device, where ammonia is introduced, so that ammonia and flue gas containing NO2 are mixed to form mixed flue gas, and the mixed flue gas flows downward through the NH3-SCR catalyst to perform an SCR reaction to complete denitration.

[0075] The beneficial effects of the present invention include:

[0076] 1. The lanthanum strontium cobalt iron perovskite catalyst provided by the present invention can be used to catalyze the NO oxidation reaction, achieving efficient catalytic oxidation of NO to NO at a relatively low temperature. x The catalyst preparation method utilizes the sol-gel method, which has a simple process and low cost and has a good application prospect.

[0077] 2. The catalytic system formed by combining the lanthanum strontium cobalt iron perovskite catalyst and the NH3-SCR catalyst in the present invention can be used for a rapid NH3-SCR-assisted denitrification method, which can efficiently catalyze the reduction of nitrogen oxides (NOx) at a relatively low temperature and significantly reduce the NH3-SCR reaction temperature, thereby saving the energy consumption required for heating and the large amount of CO2 generated thereby. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 This is the XRD pattern of the LSCF-1 catalyst of Example 1. DETAILED DESCRIPTION

[0079] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0080] Comparative Example 1

[0081] This comparative example provides an NH3-SCR catalyst, and the preparation method of the catalyst comprises:

[0082] 12.25 1g of metatitanic acid was used as a precursor of TiO2, added to a mixed solution of 0.531g of ammonium metatungstate and 0.034g of ammonium metavanadate, stirred evenly, and then transferred into a high-pressure hydrothermal autoclave, reacted at 170°C for 12h, taken out and filtered, dried at 120°C for 12h, and calcined at 550°C in air atmosphere for 6h. The obtained catalyst was recorded as DB-VWT (hereinafter referred to as VWT catalyst). The mass fraction of V2O5 in the catalyst was 0.5wt.%, the mass fraction of WO3 was 5wt.%, and the balance was TiO2.

[0083] Comparative Example 2

[0084] This comparative example provides a perovskite NO catalyst, which is prepared by a sol-gel method. The specific preparation method includes:

[0085] Weigh 4.38 g of EDTA and add it to 100 ml of deionized water. Add ammonia water dropwise to adjust the pH value to 5. Then add 4.33 g of lanthanum nitrate hexahydrate, 2.91 g of cobalt nitrate hexahydrate and 1.92 g of CA. Stir. Add ammonia water to adjust the pH to 5. Use 40,000 Hz ultrasonic wave to assist stirring at 50°C for 8 hours to prepare Sol B1.

[0086] Sol B1 was placed in a rotary evaporator and rotary evaporated at 80°C at a speed of 40 rpm / min. After 12 hours, it became a viscous purple-red gel. The obtained gel was placed in an oven and dried at 150°C at an air pressure of 5000 Pa to obtain a dry gel.

[0087] The obtained dry gel was calcined in a muffle furnace. First, the first calcination was carried out at 350°C for 5 hours to remove organic matter such as CA and EDTA; then the temperature was raised to 800°C for a second calcination for 6 hours to obtain a perovskite catalyst, which was recorded as LC.

[0088] Comparative Example 3

[0089] This comparative example provides a perovskite NO catalyst, which is prepared by a sol-gel method. The specific preparation method includes:

[0090] Weigh 4.38 g of EDTA and add it to 100 ml of deionized water, add ammonia water to adjust the pH value to 5, then add 4.33 g of lanthanum nitrate hexahydrate, 2.32 g of cobalt nitrate hexahydrate, 0.81 g of ferric nitrate nonahydrate and 1.92 g of CA, stir, add ammonia water to adjust the pH to 5, use 40000 Hz ultrasonic assisted stirring at 50°C for 8 hours to prepare Sol B2.

[0091] Sol B2 was placed in a rotary evaporator and rotary evaporated at 80°C at a speed of 40 rpm / min. After 12 hours, it became a viscous purple-red gel. The obtained gel was placed in an oven and dried at 150°C at an air pressure of 5000 Pa to obtain a dry gel.

[0092] The obtained dry gel was placed in a muffle furnace for calcination. First, the first calcination was carried out at 350°C for 5 hours to remove organic matter such as CA and EDTA; then the temperature was raised to 800°C for a second calcination for 6 hours to obtain a perovskite catalyst, which was recorded as LCF.

[0093] Comparative Example 4

[0094] This comparative example provides a perovskite NO catalyst, which is prepared by a sol-gel method. The specific preparation method includes:

[0095] Weigh 4.38 g of EDTA and add it to 100 ml of deionized water. Add ammonia water dropwise to adjust the pH value to 5. Then add 3.03 g of lanthanum nitrate hexahydrate, 0.63 g of strontium nitrate, 2.91 g of cobalt nitrate hexahydrate and 1.92 g of CA. Stir. Add ammonia water to adjust the pH to 5. Stir at 50°C with 40,000 Hz ultrasonic wave for 8 hours to prepare Sol B3.

[0096] Sol B3 was placed in a rotary evaporator and rotary evaporated at 80°C at a speed of 40 rpm / min. After 12 hours, it became a viscous purple-red gel. The obtained gel was placed in an oven and dried at 5000 Pa pressure and 120-170°C to obtain a dry gel.

[0097] The obtained dry gel was calcined in a muffle furnace. First, the first calcination was carried out at 350°C for 5 hours to remove organic matter such as CA and EDTA; then the temperature was raised to 800°C for a second calcination for 6 hours to obtain a perovskite catalyst, which was recorded as LSC.

[0098] Example 1

[0099] This embodiment provides a lanthanum strontium cobalt iron perovskite NO catalyst, which is prepared by a sol-gel method. The specific preparation method includes:

[0100] Weigh 4.38 g of EDTA and add it to 100 ml of deionized water. Add ammonia water dropwise to adjust the pH value to 5. Then add 3.03 g of lanthanum nitrate hexahydrate, 0.63 g of strontium nitrate, 2.32 g of cobalt nitrate hexahydrate, 0.81 g of ferric nitrate nonahydrate and 1.92 g of CA. Stir. Add ammonia water to adjust the pH to 5. Stir at 50°C with 40,000 Hz ultrasonic wave for 8 hours to prepare Sol A1.

[0101] Sol A1 was placed in a rotary evaporator and rotary evaporated at 80°C at a speed of 40 rpm / min. After 12 hours, it became a viscous purple-red gel. The obtained gel was placed in an oven and dried at 5000 Pa pressure and 120-170°C to obtain a dry gel.

[0102] The obtained dry gel was placed in a muffle furnace for calcination. First, the first calcination was carried out at 350°C for 5 hours to remove organic matter such as CA and EDTA; then the temperature was raised to 800°C for a second calcination for 6 hours to obtain the perovskite catalyst, which was recorded as LSCF-1. The molecular formula of the catalyst is La 0.7 Sr 0.3 Co 0.8 Fe 0.2 O3.

[0103] Example 2

[0104] This embodiment provides a lanthanum strontium cobalt iron perovskite NO catalyst, which is prepared by a sol-gel method. The specific preparation method includes:

[0105] Weigh 4.38 g of EDTA and add it to 100 ml of deionized water. Add ammonia water dropwise to adjust the pH value to 5. Then add 3.90 g of lanthanum nitrate hexahydrate, 0.21 g of strontium nitrate, 2.32 g of cobalt nitrate hexahydrate, 0.81 g of ferric nitrate nonahydrate and 1.92 g of CA. Stir. Add ammonia water to adjust the pH to 5. Use 40,000 Hz ultrasonic wave to assist stirring at 50°C for 8 hours to prepare Sol A2.

[0106] Sol A2 was placed in a rotary evaporator and rotary evaporated at 80°C at a speed of 40 rpm / min. After 12 hours, it became a viscous purple-red gel. The obtained gel was placed in an oven and dried at 5000 Pa pressure and 120-170°C to obtain a dry gel.

[0107] The obtained dry gel was placed in a muffle furnace for calcination. First, the first calcination was carried out at 350°C for 5 hours to remove organic matter such as CA and EDTA; then the temperature was raised to 800°C for a second calcination for 6 hours to obtain the perovskite catalyst, which was recorded as LSCF-2. The molecular formula of the catalyst is La 0.9 Sr 0.1 Co 0.8 Fe 0.2 O3.

[0108] Example 3

[0109] This embodiment provides a lanthanum strontium cobalt iron perovskite NO catalyst, which is prepared by a sol-gel method. The specific preparation method includes:

[0110] Weigh 4.38 g of EDTA and add it to 100 ml of deionized water. Add ammonia water dropwise to adjust the pH value to 5. Then add 3.03 g of lanthanum nitrate hexahydrate, 0.63 g of strontium nitrate, 1.74 g of cobalt nitrate hexahydrate, 1.62 g of ferric nitrate nonahydrate and 1.92 g of CA. Stir. Add ammonia water to adjust the pH to 5. Stir at 50°C with 40,000 Hz ultrasonic wave for 8 h to prepare Sol A3.

[0111] Sol A3 was placed in a rotary evaporator and rotary evaporated at 80°C at a speed of 40 rpm / min. After 12 hours, it became a viscous purple-red gel. The obtained gel was placed in an oven and dried at 5000 Pa pressure and 120-170°C to obtain a dry gel.

[0112] The obtained dry gel was placed in a muffle furnace for calcination. First, the first calcination was carried out at 350°C for 5 hours to remove organic matter such as CA and EDTA; then the temperature was raised to 800°C for a second calcination for 6 hours to obtain the perovskite catalyst, which was recorded as LSCF-3. The molecular formula of the catalyst is La 0.7 Sr 0.3 Co 0.6 Fe 0.4 O3.

[0113] The particle size of the catalysts prepared in Example 1, Example 2 and Example 3 is 0.25-1 μm, and the crystallinity of the above catalysts is above 70%.

[0114] Test Example 1

[0115] This test example provides a catalytic activity test of the catalyst of Comparative Example 1.

[0116] NO oxidation reaction: Catalytic evaluation experiments were conducted in a fixed bed reactor at atmospheric pressure. 1 g of VWT catalyst was weighed, the temperature was raised to 300 °C at 2 ° / min, N2 was purged for 2 h, the temperature was lowered to room temperature, and the reaction gas was introduced. The composition of the reaction gas was: NO 500 ppm, O2 volume fraction 10%, H2O volume fraction 5%, and the rest was nitrogen as the balance gas. The reaction gas was heated to 0.15 MPa and the air velocity was 20000 h -1 The temperature was raised to 150-300°C for reaction. All collected NO2 was detected. The results are shown in Table 1.

[0117] NO oxidation and NH3-SCR coupling reaction: Catalytic evaluation experiments were conducted in a fixed bed reactor at atmospheric pressure. 1 g of VWT catalyst was weighed, the temperature was raised to 300 °C at 2 ° / min, N2 was purged for 2 h, the temperature was lowered to room temperature, and the reaction gas was introduced. The composition of the reaction gas was: 500 ppm each of NO and NH3, 10% by volume of O2, 5% by volume of H2O, and the rest was nitrogen as the balance gas. At 0.15 MPa and a space velocity of 20000 h -1 The reaction was carried out under the conditions of 150-300°C and all the collected NO was detected. The results are shown in Table 2.

[0118] Test Example 2

[0119] This test example provides a catalytic activity test of the catalyst of Comparative Example 2.

[0120] NO oxidation reaction: Catalytic evaluation experiment was carried out in a fixed bed reactor at normal pressure. Weigh 0.5g LC catalyst + 0.5g VWT catalyst, heat to 300℃ at 2° / min, purge with N2 for 2h, cool to room temperature, and introduce reaction gas. The composition of the reaction gas is: NO 500ppm, O2 volume fraction 10%, H2O volume fraction 5%, and the rest is nitrogen as balance gas. At 0.15MPa, space velocity 20000h -1 The temperature was raised to 150-300°C for reaction. All collected NO2 was detected. The results are shown in Table 1.

[0121] The NO oxidation reaction performance was evaluated by replacing the above combination of 0.5 g LC catalyst + 0.5 g VWT catalyst with 0.5 g LC catalyst. The results are shown in Table 2.

[0122] NO oxidation and NH3-SCR coupling reaction: weigh 0.5g LC catalyst + 0.5g VWT catalyst, where the LC catalyst is placed before the VWT catalyst (it means that the LC catalyst contacts the reaction gas before the VWT catalyst, the same below), heat up to 300℃ at 2° / min, purge with N2 for 2h, cool down to room temperature and pass the reaction gas, the composition of the reaction gas is: NO and NH3 500ppm each, O2 volume fraction is 10%, H2O volume fraction is 5%, and the rest is nitrogen as the balance gas. At 0.15MPa, air velocity 20000h -1 The reaction was carried out under the conditions of 150-300°C and all the collected NO was detected. The results are shown in Table 3.

[0123] Test Example 3

[0124] This test example provides a catalytic activity test of the catalyst of Comparative Example 3.

[0125] NO oxidation reaction: Catalytic evaluation experiment was carried out in a fixed bed reactor at atmospheric pressure. Weigh 0.5g LCF catalyst + 0.5g VWT catalyst, where LCF catalyst was placed before VWT catalyst, and heated to 300℃ at 2° / min, N2 was purged for 2h, cooled to room temperature, and reactant gas was introduced. The reactant gas composition was: NO 500ppm, O2 volume fraction 10%, H2O volume fraction 5%, and the rest was nitrogen as balance gas. At 0.15MPa, air velocity 20000h -1 , and the temperature was raised to 150-300℃ for reaction. All collected NO2 was detected. The results are shown in Table 1.

[0126] 0.5 g of LCF catalyst was used to replace the above combination of 0.5 g of LFC catalyst + 0.5 g of VWT catalyst to evaluate the NO oxidation reaction performance. The results are shown in Table 2.

[0127] NO oxidation and NH3-SCR coupling reaction: weigh 0.5g LC catalyst + 0.5g VWT catalyst, where the LCF catalyst is placed before the VWT catalyst, heat to 300℃ at 2° / min, purge with N2 for 2h, cool to room temperature, introduce 500ppm of NO and NH3, 10% O2 volume fraction, 5% H2O volume fraction, and the rest is nitrogen as balance gas. -1 The reaction was carried out under the conditions of 150-300°C and all the collected NO was detected. The results are shown in Table 3.

[0128] Test Example 4

[0129] This test example provides a catalytic activity test of the catalyst of Comparative Example 4.

[0130] NO oxidation reaction: Catalytic evaluation experiment was carried out in a fixed bed reactor at normal pressure. Weigh 0.5g LSC catalyst + 0.5g VWT catalyst, where LSC catalyst was placed before VWT catalyst, and heated to 300℃ at 2° / min, N2 was purged for 2h, cooled to room temperature, and reactant gas was introduced. The reactant gas composition was: NO 500ppm, O2 volume fraction 10%, H2O volume fraction 5%, and the rest was nitrogen as balance gas. At 0.15MPa, air velocity 20000h -1 The temperature was raised to 150-300°C for reaction. All collected NO2 was detected. The results are shown in Table 1.

[0131] 0.5 g of LSC catalyst was used to replace the above combination of 0.5 g of LSC catalyst + 0.5 g of VWT catalyst to evaluate the NO oxidation reaction performance. The results are shown in Table 2.

[0132] NO oxidation and NH3-SCR coupling reaction: weigh 0.5g LSC catalyst + 0.5g VWT catalyst, where the LSC catalyst is placed before the VWT catalyst, heat to 300℃ at 2° / min, purge with N2 for 2h, cool to room temperature and introduce reaction gas, the composition of the reaction gas is: NO and NH3 500ppm each, O2 volume fraction is 10%, H2O volume fraction is 5%, and the rest is nitrogen as balance gas. At 0.15MPa, air velocity 20000h -1 The reaction was carried out under the conditions of 150-300°C and all the collected NO was detected. The results are shown in Table 3.

[0133] Test Example 5

[0134] This test example provides a catalytic activity test of the catalyst in Example 1.

[0135] NO oxidation reaction: Catalytic evaluation experiment was carried out in a fixed bed reactor at normal pressure. Weigh 0.5g LSCF-1 catalyst + 0.5g VWT catalyst, where LSCF-1 catalyst was placed before VWT catalyst. The temperature was raised to 300℃ at 2° / min and N2 was purged for 2h. The temperature was lowered to room temperature and the reaction gas was introduced. The composition of the reaction gas was: NO 500ppm, O2 volume fraction 10%, H2O volume fraction 5%, and the rest was nitrogen as balance gas. At 0.15MPa and air velocity 20000h - 1 The temperature was raised to 150-300°C for reaction. All collected NO2 was detected. The results are shown in Table 1.

[0136] 0.5 g of LSCF-1 catalyst was used to replace the above combination of 0.5 g of LSCF-1 catalyst + 0.5 g of VWT catalyst to evaluate the NO oxidation reaction performance. The results are shown in Table 2.

[0137] NO oxidation and NH3-SCR coupling reaction: weigh 0.5g LSCF-1 catalyst + 0.5g VWT catalyst, where LSCF-1 catalyst is placed before VWT catalyst, heat to 300℃ at 2° / min, purge with N2 for 2h, cool to room temperature and introduce reaction gas, the composition of reaction gas is: NO and NH3 500ppm each, O2 volume fraction is 10%, H2O volume fraction is 5%, and the rest is nitrogen as balance gas. -1 The temperature was raised to 150-300°C for reaction, and all collected NO was detected. The results are shown in Table 3. The above coupling reaction of NO oxidation and NH3-SCR is a fast NH3-SCR-assisted low-temperature denitrification method.

[0138] Test Example 6

[0139] This test example provides a catalytic activity test of the catalyst in Example 2.

[0140] NO oxidation reaction: Catalytic evaluation experiment was carried out in a fixed bed reactor at atmospheric pressure. Weigh 0.5g LSCF-2 catalyst + 0.5g VWT catalyst, where LSCF-2 catalyst was placed before VWT catalyst, heated to 300℃ at 2° / min, purged with N2 for 2h, cooled to room temperature, and introduced reaction gas. The composition of the reaction gas was: NO 500ppm, O2 volume fraction 10%, H2O volume fraction 5%, and the rest was nitrogen as balance gas. At 0.15MPa, space velocity 20000h - 1 The temperature was raised to 150-300°C for reaction. All collected NO2 was detected. The results are shown in Table 1.

[0141] 0.5 g of LSFC-2 catalyst was used to replace the above combination of 0.5 g of LSFC-2 catalyst + 0.5 g of VWT catalyst to evaluate the NO oxidation reaction performance. The results are shown in Table 2.

[0142] NO oxidation and NH3-SCR coupling reaction: weigh 0.5g LSCF-2 catalyst + 0.5g VWT catalyst, where LSCF-2 catalyst is placed before VWT catalyst, heat to 300℃ at 2° / min, purge with N2 for 2h, cool to room temperature and introduce reaction gas, the composition of reaction gas is: NO and NH3 500ppm each, O2 volume fraction is 10%, H2O volume fraction is 5%, and the rest is nitrogen as balance gas. -1 The temperature was raised to 150-300°C for reaction, and all collected NO was detected. The results are shown in Table 3. The above coupling reaction of NO oxidation and NH3-SCR is a fast NH3-SCR-assisted low-temperature denitrification method.

[0143] Test Example 7

[0144] This test example provides a catalytic activity test of the catalyst in Example 3.

[0145] NO oxidation reaction: Catalytic evaluation experiment was carried out in a fixed bed reactor at atmospheric pressure. Weigh 0.5g LSCF-3 catalyst + 0.5g VWT catalyst, where LSCF-3 catalyst was placed before VWT catalyst, and heated to 300℃ with N2 2° / min for 2h, cooled to room temperature and introduced reaction gas. The composition of the reaction gas was: NO 500ppm, O2 volume fraction 10%, H2O volume fraction 5%, and the rest was nitrogen as balance gas. At 0.15MPa, space velocity 20000h -1 The temperature was raised to 150-300°C for reaction. All collected NO2 was detected. The results are shown in Table 1.

[0146] 0.5 g of LSFC-3 catalyst was used to replace the above combination of 0.5 g of LSFC-3 catalyst + 0.5 g of VWT catalyst to evaluate the NO oxidation reaction performance. The results are shown in Table 2.

[0147] NO oxidation and NH3-SCR coupling reaction: weigh 0.5g LSCF-3 catalyst + 0.5g VWT catalyst, where LSCF-3 catalyst is placed before VWT catalyst, heat to 300℃ at 2° / min, purge with N2 for 2h, cool to room temperature and introduce reaction gas, the composition of reaction gas is: NO and NH3 500ppm each, O2 volume fraction is 10%, H2O volume fraction is 5%, and the rest is nitrogen as balance gas. -1The temperature was raised to 150-300°C for reaction, and all collected NO was detected. The results are shown in Table 3. The above coupling reaction of NO oxidation and NH3-SCR is a fast NH3-SCR-assisted low-temperature denitrification method.

[0148] The NO conversion rate in Table 1 and Table 2 is the conversion rate of NO to NO2 in the NO oxidation reaction, and the calculation method is:

[0149]

[0150] The NO conversion rate in Table 3 is the conversion rate of NO in the entire denitrification process, and its calculation method is:

[0151]

[0152] NO 2outlet Represents the volume concentration of NO2 at the outlet, NO inlet represents the volume concentration of NO at the inlet, NO outlet Represents the volume concentration of NO at the outlet.

[0153] Table 1 NO oxidation reaction activity

[0154]

[0155] Table 2 NO oxidation reaction activity

[0156]

[0157] Table 3 NH3-SCR reaction activity

[0158]

[0159] Figure 1 The XRD pattern of the LSCF-1 catalyst of Example 1 is shown in FIG. Figure 1 It can be seen that the LSCF-1 catalyst has the characteristic diffraction peak of perovskite, indicating that the catalyst of Example 1 has a perovskite structure. It has been measured that the catalysts of Examples 2 and 3 also have a perovskite structure.

[0160] As can be seen from Table 1, at 150°C and 200°C, the NO reaction activity of the VWT catalyst is very low, indicating that NO is almost not oxidized to NO2; and after the NO oxidation catalyst is introduced to form the composite catalyst, the activity of NO oxidation to NO2 has been significantly improved. Comparing the composite catalytic systems of Comparative Examples 2-4 and Examples 1-3, it can be seen that the combination of the LSFC series catalyst and the VWT catalyst has a high NO reaction activity, among which the reaction activity improvement effect of the LSFC-1+VWT catalyst is the most obvious.

[0161] It can be seen from Table 2 that among the six individual perovskite catalysts (Comparative Examples 2-4, Examples 1-3), the LSCF series catalysts all have high NO oxidation reaction activity, among which the LSCF-1 catalyst has the highest NO oxidation reaction activity. Combining the results of Tables 1 and 2, it can be seen that during the NO oxidation reaction, the VWT catalyst has no obvious effect on the reaction activity, and the LSCF catalyst (especially at 150°C and 300°C) mainly contributes to the reaction activity.

[0162] As can be seen from Table 3, at 150°C and 200°C, the NH3-SCR reaction activity of the VWT catalyst is only 10% and 48%, while after the introduction of the NO oxidation catalyst to form the composite catalyst, because it can oxidize NO to NO2, a rapid NH3-SCR reaction occurs, resulting in a significant increase in the denitrification efficiency. Comparing the composite catalytic systems, it can be seen that the combination of the LSFC series catalyst and the VWT catalyst has a high NH3-SCR reaction activity, among which the LSCF-1+VWT composite catalyst has the highest efficiency.

Claims

1. A lanthanum strontium cobalt iron perovskite catalyst, the molecular formula of the catalyst is La x Sr 1-x Co y Fe 1-y O3, where x is 0.7-1, y is 0.6-1.

2. The lanthanum strontium cobalt iron perovskite catalyst according to claim 1, wherein The particle size of the lanthanum strontium cobalt iron perovskite catalyst is 0.25 μm-1 μm; the crystallinity of the lanthanum strontium cobalt iron perovskite catalyst is ≥70%.

3. A method for preparing the lanthanum strontium cobalt iron perovskite catalyst according to claim 1 or 2, the preparation method comprising: mixing a metal salt precursor with a chelating agent to obtain a raw material solution; removing the solvent from the raw material solution to form a gel, drying the gel to form a xerogel, and calcining the xerogel to obtain the lanthanum strontium cobalt iron perovskite catalyst; Wherein, the metal salt precursor includes lanthanum salt, strontium salt, cobalt salt and iron salt; The molar ratio of the chelating agent to the metal ions in the metal salt precursor is 1-3:

1.

4. The preparation method according to claim 3, wherein The chelating agent includes citric acid and / or ethylenediaminetetraacetic acid.

5. The preparation method according to claim 3, wherein: The method for removing the solvent includes rotary evaporation, the rotation speed of the rotary evaporation is 10rpm / min-60rpm / min, the temperature of the rotary evaporation is 50℃-90℃, and the time of the rotary evaporation is 8h-24h.

6. The preparation method according to claim 3, wherein: The roasting includes a first roasting and a second roasting performed sequentially; The temperature of the first calcination is 300°C-400°C, and the time of the first calcination is 3h-7h; The temperature of the second calcination is 750° C.-850° C., and the time of the second calcination is 5 h-8 h.

7. A NO oxidation catalyst comprising the lanthanum strontium cobalt iron perovskite catalyst according to claim 1 or 2 or made from the lanthanum strontium cobalt iron perovskite catalyst.

8. A composite catalytic system comprising the NO oxidation catalyst and the NH3-SCR catalyst according to claim 7; The mass ratio of the NO oxidation catalyst to the NH3-SCR catalyst is 1:1-2.

9. The composite catalytic system according to claim 8, wherein: The NH3-SCR catalyst includes a V2O5-WO3 / TiO2 catalyst; Taking the total mass of the V2O5-WO3 / TiO2 catalyst as 100%, in the V2O5-WO3 / TiO2 catalyst: the mass fraction of V2O5 is 0.1wt.%-1wt.%, the mass fraction of WO3 is 1wt.%-10wt.%, and the remainder is TiO2 as a carrier.

10. The composite catalytic system according to claim 9, wherein: The preparation method of the V2O5-WO3 / TiO2 catalyst comprises: mixing a titanium source, a vanadium source and a tungsten source, performing a hydrothermal reaction, filtering, drying and calcining to obtain the V2O5-WO3 / TiO2 catalyst; The temperature of the hydrothermal reaction is 150°C-250°C, and the time of the hydrothermal reaction is 8h-24h; The calcination temperature is 400° C.-650° C., and the calcination time is 4 h-12 h.

11. A low-temperature denitration method, the method comprising: Using the composite catalytic system according to any one of claims 8 to 10 as a catalyst, introducing raw flue gas containing NO and NH3 to perform denitration; The NO oxidation catalyst and the NH3-SCR catalyst of the composite catalytic system are placed separately so that the raw flue gas contacts the NO oxidation catalyst first and then contacts the NH3-SCR catalyst.

12. The low-temperature denitration method according to claim 11, wherein: The denitration method comprises: introducing raw flue gas, allowing the raw flue gas to contact with a NO oxidation catalyst to perform a NO oxidation reaction; mixing the flue gas after the NO oxidation reaction with NH3 to form a mixed flue gas, and allowing the mixed flue gas to contact with an NH3-SCR catalyst to perform an SCR reaction to complete denitration.

13. The low-temperature denitration method according to claim 11 or 12, wherein: The raw flue gas contains NO, O2, H2O, SO2 and N2; The raw flue gas comprises: NO with a concentration of 100ppm-1000ppm, O2 with a volume fraction of 5%-10%, H2O with a volume fraction of 2%-5%, SO2 with a concentration of 0-200ppm, and the remainder N2.

14. The low-temperature denitration method according to claim 11 or 12, wherein: The molar ratio of NO to NH3 in the raw flue gas is 1:1-1.2; The ratio of the molar amount of NO in the raw flue gas to the mass of the composite catalyst system is 1 mol: 0.5 g-2 g.

15. The low-temperature denitration method according to claim 11 or 12, wherein: The reaction temperature of the denitration is 150°C-450°C, the reaction pressure of the denitration is 0.1MPa-0.6MPa, and the reaction space velocity of the denitration is 5000h -1 -160000h -1 .